Mitosis and its regulation - Alfredo de Jesús Rodríguez-Gómez; Sara Frías-Vázquez (Instituto Nacional de Pediatría, 2014)
Cell division by mitosis is essential for the development of organisms and their reproduction; it is also necessary that each new cell is genetically identical to that from which it comes. In eukaryotes this is achieved by the presence of complex mechanisms that ensure the integrity of genomic material and their proper segregation during mitosis. The traditional view of mitosis has been divided into different stages that were characterized by morphological studies in dividing cells; advances in molecular biology have led beyond this characterization, so that we now know a range of participant molecules. This article will discuss the process of mitosis, both at the cellular and molecular level and a brief summary of the molecular players that regulate this process.